A Pilot study on a Cross Sectional Investigation of Science and Engineering Undergraduates: Motivation towards Learning English in Pakistan - Siming, Insaf Ali; ., Muhammad Mujtaba Asad; ., Ajab Ali Lashari (Journal of Education and Vocational Research, 2015)
This research paper aims at to describe the results of pilot study on â€œA cross sectional investigation of Science and Engineering undergraduatesâ€™ motivation towards learning English in Pakistanâ€. The results of this research probably are useful and beneficial in the sense to test the instrument proposed for current study in particular and to provide recommendations for full study in general. Moreover Mix method design both qualitative and quantitative has been proposed for full study. But in piloting study the researchers only administered survey questionnaire in order to test the instrument. The researchers consulted the various studies on learnersâ€™ motivational studies and used a modified questionnaire based on the Attitude Motivation Test Battery (AMTB) by Robert Gardner and the three stage model of Dorneyi. For the sampling researchersâ€™ selected convenience random sampling taking the names form hat policy was adopted. Questionnaire was divided in three parts, Part one of the questionnaire contained informantsâ€™ demographic information. Second part of questionnaire contained ninety six closed ended items, and third part of the questionnaire contain three open ended questions. The population of this pilot study was Science and engineering students from Quaid-e-Awam University of Engineering and Technology. For reliability and validity check, all the data was interred in SPSS version 20 and cronbachâ€™s Alpha reliability of questionnaire remained 0.920. This study intended to achieve the following aims and objectives (1) identify the motivational level of Science and Engineering undergraduatesâ€™ towards learning English language (2) Establish the factors that effects undergraduatesâ€™ motivation towards second language (L2) (3) Compare the motivational level between Science and Engineering undergraduatesâ€™ towards learning English language. In later section of paper, a complete visual illustration of demographic information of initial findings based on gender, mother tongue, origin, departments and institutional status is graphically presented. Finally, it is highly recommended from the results obtained from the pilot study that instrument used in this study is valid and reliable and can be confidently used for full study. Due to its excellent level of validity, reliability and suitability